Pendidikan Aswaja Menjawab Tantangan Era Milenial - Zaenal Abidin (Institut Agama Islam Sahid (INAIS) Bogor, 2020)
This research examines the role of education Aswaja in efforts to answer the challenges of the millennial era. The millennial or millennium generation is known as Generation Y. This generation uses a lot of social media such as Facebook, Twitter, and Instagram. In other words, the millennial generation is the generation that grew up in the internet and online era. Aswaja education is believed to have an important role in facing challenges in the millennial era. The data presented in this article comes from observation, interviews and literature review related to the topic of writing. The argument built in this paper is that the reconstruction and actualization of the values contained in Aswaja Education can be internalized firmly within a person. An important strategy that can be taken to deal with the millennial era is socialization and internalization of Aswaja through education and social media, for example by applying ASWAJA's course subjects in Higher Education. Thus the millennial generation has the opportunity to have a moderate understanding of religion and be able to face the millennial era.